THE EFFECT OF MOTIVATIONAL FACTORS ON USAGE OF PIRATED SOFTWARE AMONG LECTURERS - Basrul Abdul Majid; Hazrullah Hazrullah; Yulia Maulida (UIN Ar-Raniry, 2021)
This study aims to determine the influence of motivational factors in using pirate software among lecturers in one of the faculty of education and teacher training in Aceh. The research method that was applied in this study is a quantitative method and it uses simple random sampling for collecting data. It was obtained by distributing the instrument to lecturers with the number of samples determined using the Slovin formula is 68 respondents. After passing the validity and reliability testing phase, data is analyzed by using Pearson Product Moment Correlation. The result explained that there was a significant influence between motivational factors and using pirated software. The final result of the correlation test for two variables with a coefficient value of 0.876 and a significant level of 0.000 with a very good level of relationship category.